Strategi Pengembangan Kemampuan Public Speaking Dan Dampaknya Terhadap Self Confidence Peserta Didik : (Studi Komparatif MAN 1 Banda Aceh dan MAN 4 Aceh Besar) - Rifki Rifki (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to reveal strategies for developing public speaking skills and describe the impact of public speaking skills on students' self-confidence at MAN 1 Banda Aceh and MAN 4 Aceh Besar. In this research, the methodology used is qualitative with a descriptive approach. The research results show that: (1) The strategy for developing students' public speaking skills at MAN 1 Banda Aceh and MAN 4 Aceh Besar goes through several stages including: planning, methods, implementation and evaluation. (2) The impact of students' public speaking skills at MAN 1 Banda Aceh and MAN 4 Aceh Besar has provided significant results for students. The aspects that include include: being confident in your own abilities, being able to make your own decisions, having a positive feeling about yourself and having the courage to express your opinion to other people. Through this, students succeed in improving their public speaking skills. They are able to organize thoughts clearly, regulate the flow of presentations, and use effective communication techniques. This is related to the application of interpersonal communication theory and effective presentation theory presented in the training. Apart from that, students also succeeded in managing nervousness and anxiety when communicating. They gain a better understanding of the sources of nervousness and techniques for dealing with anxiety. Breathing regulation exercises, muscle relaxation, and other self-control techniques based on communication anxiety theory help students overcome these challenges.